Analisis Pengenaan Pajak Pertambahan Nilai (PPN) pada Daging Premium: Usulan Desain Kebijakan - Helmalia Cahyani; Riko Riandoko (Directorate General of Taxes, 2026)
The exemption of value-added tax (VAT) on all types of meat is considered inconsistent with the principle of fairness due to the significant price disparity between premium meat and meat for general consumption. Although the issue of imposing VAT on premium meat has emerged since the enactment of the HPP Law, no specific technical regulation has yet been established. This study aims to analyse the policy considerations for imposing VAT on premium meat and to formulate a policy design to support its implementation. Using a descriptive qualitative approach with data collected through triangulation, the study finds that the policy can be considered based on several factors, including fiscal burdens arising from tax expenditure, inequality in the distribution of tax facilities, and the need to optimise state revenue. The policy is also supported by the existing legal framework under the HPP Law. In terms of policy design, the analysis proposes the use of cut-based classification criteria to define the taxable object while from the perspective of the collection mechanism, the specific VAT scheme is considered more advantageous as it is administratively simpler and has the potential to generate higher state revenue.